1995
DOI: 10.1111/j.1399-6576.1995.tb04232.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct cadiac electorphysiologic effects of sufentanil and vecuronium in isolated guinea‐pig hearts

Abstract: Sufentanil and vecuronium are commonly used simultaneously in anaesthesia. Bradycardia and asystole have been described immediately after the administration of these two compounds. Therefore, the purpose of the present study was to evaluate the direct cardiac effects of sufentanil and vecuronium in all parts of the cardiac pacemaker and conduction system. The electrophysiological effects of sufentanil and vecuronium were studied in isolated spontaneously beating guinea-pig hearts perfused by the method of Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Decrease in post‐ischaemic contractile function reflects, at least in part, Ca 2+ overload during reperfusion 17 with impaired myofibrillar sensitivity to Ca 2+ 18 . Remifentanil may reduce the intracellular [Ca 2+ ], 19 and the electrophysiological effects of sufentanil are comparable to that of unspecific calcium antagonists 20 . However, at clinically relevant concentrations, we have previously demonstrated that remifentanil and sufentanil did not exert any negative inotropic or lusitropic effects on isolated human right trabeculae, strongly suggesting that they do not modify the Ca 2+ flux 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in post‐ischaemic contractile function reflects, at least in part, Ca 2+ overload during reperfusion 17 with impaired myofibrillar sensitivity to Ca 2+ 18 . Remifentanil may reduce the intracellular [Ca 2+ ], 19 and the electrophysiological effects of sufentanil are comparable to that of unspecific calcium antagonists 20 . However, at clinically relevant concentrations, we have previously demonstrated that remifentanil and sufentanil did not exert any negative inotropic or lusitropic effects on isolated human right trabeculae, strongly suggesting that they do not modify the Ca 2+ flux 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion pressure was set to 80 mmHg. Left ventricular developed pressure and derivatives, end‐diastolic pressure, epicardial electrocardiogram and perfusion pressure were recorded on a personal computer (7, 8). Coronary flow was measured by the timed collection of perfusate dripping from the right heart into a graduated cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…No studies have been reported in humans to evaluate the effects of sufentanil on QT interval, but a case report showed QT interval prolongation after 24 μg/kg sufentanil, in a patient undergoing cardiac surgery [92]. However, an experimental study on guinea pig hearts showed that sufentanil has no effect on repolarization and another on canine purkinje fibres demonstrated significant lengthening of QT duration caused by high concentrations of sufentanil concentration [93,94]. According to Kweon et al [95], 1 μg/kg remifentanil not only does not prolong QT but also has preventive effects on QT prolongation following laryngoscopy and tracheal intubation.…”
Section: Fentanylmentioning
confidence: 99%